Affects in 21st-Century British Theatre
XI, 284 p. 1 illus.
Keywords: This book explores the various manifestations of affects in British theatre of the 21st century. The introduction gives a concise survey of existing and emerging theoretical and research trends and argues in favour of a capacious understanding of affects that mediates between more autonomous and more social approaches. The twelve chapters in the collection investigate major works in Britain by playwrights and theatre makers including Mojisola Adebayo, Mike Bartlett, Alice Birch, Caryl Churchill, Tim Crouch and Andy Smith, Rachel De-lahay, Reginald Edmund, James Fritz, David Greig, Idris Goodwin, Zinnie Harris, Kieran Hurley, Lucy Kirkwood, Anders Lustgarten, Yolanda Mercy, Anthony Neilson, Lucy Prebble, Sh!t Theatre, Penelope Skinner, Stef Smith, Kae Tempest and debbie tucker green. The interpretations identify significant areas of tension as they relate affects to the fields of cognition, politics and hope. In this, the chapters uncover interrelations of thought, intention and empathy; they reveal the nexus between identities, institutions and ideology; and, finally, they explore how theatre can accomplish the transition from a sense of crisis to utopian visions.